The Lippard Effect. The Inertia of The Discourse and Institutions - Krochmalny, Pablo (2013)
The resonance of Lucy Lippard's discourse reached the exhibition "Open Work in Latin America, New York & Beyond: Conceptualism Reconsidered, 1967-1978" curated by Harper Montgomery at Hunter College. History anchors itself once again in the shelves of conceptual art. For the lovers of conspiracies, conceptualism is a complex, non-linear phenomenon. It can't be reduced to a chronology but crystallises into networks of power. The story of Lippard persists beyond the evidences reaped by the history of art in the last decade. One demonstration of the standing of an institutional collection like that of Cisneros, ought to be carefully examining the investigations into conceptualism that are being developed in diverse parts of the world, and not remaining petrified in the face of the advances made in the investigation of art and curatorial practices. An institutional collection is not built up out of commercial interests nor personal caprices, but through historical investigation.